THE RELEVANCE OF THE STUDY OF THE PRIBREZHNY VOLCANIC COMPLEX IN THE CONTEXT OF THE HISTORY INVESTIGATIONS OF SOUTH KAMCHATKA - O. V. Bergal-Kuvikas; A. N. Rogozin (Геодинамика и тектонофизика)
The present paper contains a review of publications, geological maps and reports on the study of the Pribrezhny volcanic complex of South Kamchatka. The Pribrezhny volcanic complex is comprised of a number of closeset volcanic massifs stretching chain-like along the narrow coastline of the Beregovoy ridge from the Avacha Bay to the Vestnik Bay. The relevance of the work is related to the necessity of revising the geodynamic history of formation of the study area which stems from emergence of some fragmentary, contradictory information about magmatic complexes of South Kamchatka. The paper presents the data on magmatic rocks penetrated in the coastal cliffs of South Kamchatka. Consideration is being given to their formation conditions in the context of a once-popular theory of geosynclines and in that of plate tectonics. Based on the review, several open research problems are formulated concerning the undetermined propagation limits of the Pribrezhny volcanic complex and unknown time intervals of its formation, and the lack of mineralogical and isotopic-geochemical studies of magmatic rocks. A separate research problem is the formation of transitional zone between the continental margin of Kamchatka and the Kuril Island Arc. The paper shows the relevance of the study of the Pribrezhny volcanic complex of South Kamchatka and proposes possible solutions to the research problems. A detailed mapping of the junction zone of Pribrezhny volcanic complex of South Kamchatka and the Kronotsky terrain near the Malko-Petropavlovsk zone of transverse dislocations will make it possible to refine the age and kinematics of their relationship. Determination of rare elements and strontium, neodymium and lead isotopes will provide a possibility to clarify the nature of magmatism as compared to heterochronous volcanic series of South Kamchatka. The data obtained will be needed to study magmogeneration conditions for acid volcanism of South Kamchatka and monogenic volcanism of the Malko-Petropavlovsk zone of transverse dislocations. The paleomagnetic studies, along with dating of rock absolute age, will help to reconstruct the paleolatitude of formation of the Pribrezhny volcanic complex and to restore the geodynamic evolution of formation of South Kamchatka.